Pengaruh Kompetensi dan Kerja Sama Tim Terhadap Kinerja Pegawai Desa Karyamukti Kecamatan Lemahabang - Iis Listiani; Asep Jamaludin; Nandang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the current era of globalization, human resource management has a very crucial role in increasing the efficiency of resource use within the organization to achieve common goals. In this case, the influence provided by competence and teamwork supports the optimization and improvement of employee performance. Therefore, this research aims to find out, analyze and explain the influence of Competency and Teamwork on Employee Performance. The research method used is verification analysis with a quantitative approach. The sampling method used in this research was using a non-probability sampling method with a saturated sampling technique because the sample size was less than 100 people, so all members of the population were sampled. Research data was obtained by distributing questionnaires via Google Form to 45 respondents from Karyamukti Village employees, Lemahabang District. Then, the data analysis method used is path analysis (Path Analysis) with the help of SPSS 23 software. The results of the discussion in this research show that there is a correlation between the Competency and Teamwork variables. There is a partially significant positive influence of each variable between Competence and Teamwork on Employee Performance. And there is also a significant positive influence simultaneously on the Competency and Teamwork variables on Employee Performance.